IMPLICATION OF ENGLISH VOCABULARY INSTRUCTION TROUGH PICTURES FOR ELEMENTRY STUDENTS - Muflihah, Tatik; Authar, Nailul (Universitas Islam Lamongan, 2019)
Vocabulary instruction in elementary students differs from other level of education. It aims to empower them understand English vocabulary related to their surroundings.This study focuses on the implication of vocabulary instruction in elementary students through pictures. The use of pictures initiate and activate students curiosity on topic. This study focuses on the use of pictures in learning vocabulary to elementary students. The data collection technique was in the form of observation and field note in one of state Elementary School (SDN) in Surabaya. The study found that picture game is useful to empower students in learning English vocabulary. In addition, students are able not only to write the words correctly, but also to construct simple sentence. This study provides suggestionto integrate picturesin learning vocabulary.Keywords: Vocabulary, Instruction, Elementary Students